Design and implementation a novel single switch high gain DC-DC converter based on coupled inductor with low-ripple input current - Barmoudeh, Farid; Ajami, Ali; Sutikno, Tole (Institute of Advanced Engineering and Science, 2023)
A novel high-gain and high-efficiency direct current to direct current (DC-DC) converter is introduced in this paper. The presented converter is suitable for low-voltage renewable energy resources such as photovoltaic (PV) and fuel cell (FC). The existence of series inductance with the input source ensures continuous and low-ramp input current, which is important for extracting maximum power from resources. Using coupled inductor technology and an intermediate capacitor in the suggested converter leads to a high gain voltage. In the presented topology for recovering energy from the leakage inductor, reducing voltage stress on the power switch, and so decreasing overall converter losses, a passive clamp circuit is used. The suitable operation range of duty cycle in the converter, besides the leakage inductor, decreases the problem of reverse recovery in diodes. The low value of the leakage inductor and the low volume and cost of the proposed converter are due to the low turn ratio of the coupled inductor. Details of the operation principles of the proposed converter have been discussed in this paper. The presented simulation and laboratory prototype results verify the theoretical analysis and performance of the suggested topology.